2016
DOI: 10.1039/c6em00215c
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dynamics of coarse and fine particulate matter at and around signalised traffic intersections

Abstract: The understanding of rapidly evolving concentrations of particulate matter (PMC) at signalised traffic intersections (TIs) is limited, but it is important for accurate exposure assessment. We performed "mobile" and "fixed-site" monitoring of size-resolved PMCs in the 0.25-34 μm range at TIs. On-road mobile measurements were made inside a car under five different ventilation settings on a 6 km long round route, passing through 10 different TIs. Fixed-site measurements were conducted at two types (3- and 4-way) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 38 publications
2
51
0
4
Order By: Relevance
“…The increase in roadside concentrations of fine particles (PM 2.5 ) is usually dominated by exhaust emissions (Amato et al, 2009;Kumar and Goel, 2016;Kumar et al, 2018) as opposed to coarse particles (PM 2.5-10 ) coming from sources such as resuspension of road dust, brake and tyre wear (Kumar et al, 2017). With an increase in traffic density, both the concentrations of fine and coarse particles should generally increase.…”
Section: Exposure Implications Due To Flow and Dispersion Around Babymentioning
confidence: 99%
“…The increase in roadside concentrations of fine particles (PM 2.5 ) is usually dominated by exhaust emissions (Amato et al, 2009;Kumar and Goel, 2016;Kumar et al, 2018) as opposed to coarse particles (PM 2.5-10 ) coming from sources such as resuspension of road dust, brake and tyre wear (Kumar et al, 2017). With an increase in traffic density, both the concentrations of fine and coarse particles should generally increase.…”
Section: Exposure Implications Due To Flow and Dispersion Around Babymentioning
confidence: 99%
“…13 Cold starts, which are more likely to occur near residences and thus non-freeway roads, result in higher levels of pollutants generated due to catalytic converters having not reached optimal temperature to efficiently reduce emissions. 45 Another study found that PM concentrations were higher during delay periods at signalized traffic intersections compared to free-flowing traffic 17 . More research is needed to better characterize differences in near-roadway pollutants from freeways and non-freeway roadways and to determine whether differences in composition may explain the difference in observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…These near-roadway pollutants include oxides of nitrogen (NO x ), ultrafine particles, carbon monoxide (CO), EC, and gaseous and particle phase organic compounds such as polycyclic aromatic hydrocarbons (PAHs), all of which are correlated and decay sharply with increasing distance away from a roadway. 1215 Because exposure to vehicle emissions from freeways and non-freeway roads are likely to be different mixtures due to differences in proportion of heavy-duty trucks, vehicle speed, traffic volumes, and frequency of acceleration, braking, and cold starts, 1517 we investigated whether the associations varied for exposures from freeways and non-freeway roads. Furthermore, since previous studies have shown that regional air pollution is strongly associated with bronchitic symptoms, and traffic is an important contributor to regional pollution in southern California, we were interested in whether the effect of near-roadway air pollutants differed across communities with higher and lower levels of regional pollution.…”
Section: Introductionmentioning
confidence: 99%
“…DF values of 0.25 and 0.65, respectively were assumed for the purpose of estimating the deposition rate of the number of inhaled ultrafine and large particles [Sturm 2016, Joodatnia et al 2013]. For the mass of the inhaled particles, DF values were adopted from Kumar and Goel [2016] and for PM 2.5 and PM 10 amounted to respectively 0.23 and 0.88 (commuters) and 0.14 and 0.88 (pedestrians).…”
Section: Methodsmentioning
confidence: 99%